KERJA SAMA ORANG TUA DENGAN NINIK MAMAK DALAM MEMBENTUK ADAB YANG BAIK BAGI REMAJA DI JORONG KOTO GADANG KECAMATAN BASO KABUPATEN AGAM - Risma Desi; Alimir Alimir; Darul Ilmi; Jasmienti (KOLONI, 2022)
Parents have an important role in forming good manners for a child or teenager to avoid bad things, as well as ninik mamak who are obliged to guide their nephews in accordance with Q.S At-Tahrim: 6. With the cooperation between parents and ninik mamak in fostering and shaping the behavior of these teenagers so that they have good manners and can be a provision for teenagers to take their lives in the future. The problems raised were the lack of youth manners, both when speaking and in acting in the community, there were some teenagers who dressed less politely, especially teenage girls, there were some teenagers who often said dirty words in the community, there were some teenagers who lacked respect. older people, and there are some teenagers who often rebel and fight against their parents. This type of research uses descriptive qualitative research methods and is in the form of field research. The location of this research is in the Kapau Jorong Koto Gadang Hamlet and the researchers took this location because here the researchers found problems that needed to be discussed and were important to research. With key informants, namely parents and supporting informants, namely ninik mamak and teenagers. To collect data, the authors conducted observations, interviews and documentation. After the data is collected, data processing and analysis is carried out. Furthermore, testing the validity of the data by means of data triangulation. Based on the results of the research obtained, that in general there has been cooperation between parents and ninik mamak through various forms of cooperation such as group meetings or community development, through visits to ninik homes. Mamak or vice versa, via telephone, through mutual cooperation activities, through farmer group activities, through yasinan group activities, and through pasambahan training activities. Keywords: Cooperation, Parents and Ninik mamak, Forming Adab, Youth